Association between acetaminophen administration and outcomes in critically ill patients with gout and hypertension - Yi, Xiao-Qing; Xie, Bo; Hu, Yuan; Gong, Tian-Jiao; Chen, Min; Cui, Xiao-Jiao (Frontiers in Pharmacology, 2024)
Background: Acetaminophen is a commonly used medication, yet its recommendation for patients with comorbid conditions of gout and hypertension is contradictory, and the impact of its usage on clinical outcomes in real-world practical settings remains uncertain. The aim of this study was to investigate the association between acetaminophen administration and clinical outcomes in critically ill patients with gout and hypertension, utilizing real-world data.Methods: A retrospective cohort study was conducted based on the MIMIC-IV (Medical Information Mart in Intensive Care-IV) database. Adult critically ill patients with gout and hypertension were included in the analysis. The exposure was acetaminophen use during ICU stay. The primary outcome was in-hospital mortality.The secondary endpoints were frequent hospitalization, 30-day, and 60-day all-cause mortality, and incidence of hypertensive emergencies. Propensity score matching (PSM) was conducted at a 1:1 ratio. Multivariable analyses were used to adjust for confounders.The pre-matched and propensity score-matched cohorts included 2448 and 1012 patients, respectively. In the PSM analysis, in-hospital mortality was 9.7% (49/ 506) in the acetaminophen use group and 12.1% (61/506) in the no use group.Acetaminophen use was associated with a decrease in-hospital mortality (hazard ratio[HR], 0.62; 95% CI, 0.41-0.92; P=0.018). In terms of secondary endpoints, after PSM, there was no statistically significant difference for both 30-day and 60-day allcause mortality reductions in the acetaminophen use group, and HRs were 0.78 (95% CI 0.55-1.11; P=0.175), and 0.75 (95% CI 0.55-1.02; P=0.069), respectively.According to the analysis of dosage and treatment group, the use of APAP within the dosage range of 2-4g and within 3-5 days of treatment significantly reduced the mortality rate of the entire cohort and PSM cohort, with statistical differences. Subgroup analysis demonstrated that lower in-hospital mortality was consistent across different baselines (age, gender, BMI, liver disease, and renal disease), with no interactions in all subgroups (interaction p-values >0.05), thereby affirming the robustness and reliability of the findings.Acetaminophen use was associated with lower in-hospital mortality in critically ill patients with gout and hypertension. Prospective studies are needed to verify this finding.